2011
DOI: 10.1584/jpestics.g10-62
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and herbicidal activity of novel 5-chloro-3-fluoro-2-phenoxypyridines with a 1,3,4-oxadiazole ring

Abstract: A series of novel 5-chloro-3-fluorophenoxypyridines with a 1,3,4-oxadiazole ring bearing a thioether moiety was synthesized and their herbicidal activity against some graminaceous plants and crop safety were examined. Target compounds were prepared through S-substitution reaction of 5-mercapto-1,3,4-oxadiazole analogs, which were synthesized by the reaction of 2-propynyl (R)-2-[4-(5-chloro-3-fluoro-pyridin-2-yloxy)-phenoxy]propionate with hydrazine hydrate and the subsequent reaction with carbon disulfide. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…The purity of all compounds was confirmed on silica gel coated aluminum plates (Merck). The ester 1 was synthesized as previously reported method [21, 23].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The purity of all compounds was confirmed on silica gel coated aluminum plates (Merck). The ester 1 was synthesized as previously reported method [21, 23].…”
Section: Methodsmentioning
confidence: 99%
“…As part of ongoing studies on the synthesis and biological consideration of heterocycles [19–22], we wish to report the synthesis of new series of 5‐membered heterocyclic titled compounds, bearing the ( R )‐5‐(1‐(4‐(5‐chloro‐3‐fluoropyridin‐2‐yloxy)phenoxy)ethyl) and their herbicidal activities.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown that the 1,3,4-oxadiazole ring, one of the most important and well-known heterocyclic nuclei, exhibits a wide variety of pesticidal biological activities, including antibacterial, [7][8][9][10][11][12][13] antifungal, [14][15][16][17][18][19][20][21] antiviral, [21][22][23] insecticidal, [24][25][26][27] and herbicidal. 28,29 In addition, in 2005, Guimarães et al demonstrated that introduction of a 1,3,4-oxadiazole ring into target compounds could change their polarity, flexibility and metabolic stability, effectively enhancing their bioactivity. 30 Meanwhile, we have previously described the synthesis and pesticidal biological properties of a series of 1,3,4-oxadiazole derivatives (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1,3,4‐Oxadiazoles, on the other hand, are well known in literature for their versatile biological activities such as anti‐inflammatory , vasodialatory , antibacterial , antifungal , antitumor , anticonvulsant , insecticidal and herbicidal . 1,3,4‐Oxadiazoles are also known as surrogates for carboxamides, esters and carboxylic acids to improve the biological activities of consequent molecules .…”
Section: Introductionmentioning
confidence: 99%